Nivolumab plus ipilimumab in metastatic melanoma: a critical appraisal focused on specific subpopulations - Vázquez-Montero, Lucía; de la Gala, María del Carmen Álamo; de la Cruz-Merino, Luis (Frontiers in Oncology, 2023)
The development of immune checkpoint inhibitors has revolutionized the landscape of treatment of advanced melanoma in recent years. Based on the efficacy results of the phase III CheckMate 067 trial, nivolumab in combination with ipilimumab is one of the first-line standard options for advanced melanoma along with pembrolizumab, nivolumab and, recently, nivolumab plus relatlimab. Counterbalancing its efficacy, nivolumab plus ipilimumab is associated with a severe immune-related toxicity. This article will review the efficacy and safety of the nivolumab plus ipilimumab combination in advanced melanoma across phase I, II and III clinical trials that evaluated this approach. We also explore the benefit of the combination schedule across different subgroups of patients and possible predictive biomarkers for efficacy outcomes in order to elucidate which patients could be the best candidates for combination or single agent therapy. Patients with BRAF-mutant tumours, presence of asymptomatic brain metastases or negative PD-L1 status appear to reach better survival outcomes with the combination relative to single agent immunotherapy.